QUALITY OF LIFE AFTER LAPAROSCOPIC SLEEVE GASTRECTOMY USING THE BAROS AND MOOREHEAD-ARDELT QUALITY OF LIFE QUESTIONNAIRE II - Kirkil, C.; Aygen, E.; Korkmaz, M. F.; Bozan, M. B. (Springer, 2016)
[Abstract Not Available]
21st World Congress of International-Federation-for-the-Surgery-of-Obesity-and-Metabolic-Disorders (IFSO) -- SEP 28-OCT 01, 2016 -- Rio de Janeiro, BRAZIL
Keywords: Sleeve gastrectomy; BAROS; Quality of life